2011
DOI: 10.1063/1.3603966
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally quantum-state-specific dynamics of the reactions of CN radicals with organic molecules in solution

Abstract: Link to publication record in Explore Bristol Research PDF-documentThe following article has been submitted to/accepted by Journal of Chemical Physics. After it is published, it will be found at 10.1063/1.3603966 University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 34 publications
4
61
1
Order By: Relevance
“…[37][38][39][40][41][42] The interpretation of these experimental measurements has been supported by simulations of the dissociation dynamics and fates of the I and CN fragments. 41,[43][44][45][46][47][48][49] Rivera et al 39 reported a peaked feature centred at 390 nm in the UV/visible absorption spectrum after photolysis of ICN in water and ethanol that closely resembled a low resolution gas-phase BX spectrum of the CN radical.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…[37][38][39][40][41][42] The interpretation of these experimental measurements has been supported by simulations of the dissociation dynamics and fates of the I and CN fragments. 41,[43][44][45][46][47][48][49] Rivera et al 39 reported a peaked feature centred at 390 nm in the UV/visible absorption spectrum after photolysis of ICN in water and ethanol that closely resembled a low resolution gas-phase BX spectrum of the CN radical.…”
Section: Introductionmentioning
confidence: 69%
“…4(d), were supplemented by spectra of the type we have reported previously in the C-H stretching (3) region around 3260 cm -1 for other reactions. [41][42] In this region, C-H stretching excitation shifts the IR absorption bands of HCN by close to -100 cm -1 relative to the fundamental band for each additional quantum of vibration. HCN that is vibrationally excited in the C-H mode can therefore be clearly distinguished from ground vibrational level molecules in the TVAS data.…”
Section: Reaction Of Cn Radicals With Dichloromethanementioning
confidence: 97%
See 1 more Smart Citation
“…[17][18][19][20][21][33][34][35][36] This assignment is further supported by the fact there is no isotope shift when CH3CN is replaced by CD3CN. The INC(v=0) band grows with a time constant of 7.7 ± 0.7 ps in CH3CN that is commensurate with the loss of CN seen by TEAS with  = 8.5  2.1 ps, followed by a more gradual increase with a time constant of 341 ± 21 ps.…”
Section: Tvas Of Solutions Of Icn In Ch3cn Following 267 Nm Excitationmentioning
confidence: 94%
“…Complete quenching of nascent vibrational excitation by interaction with the solvent bath can take tens to hundreds of picoseconds in chloroform and dichloromethane solutions. 4,5,[17][18][19]22 Modifications of the reaction mechanism by interactions with the solvent bath include formation of complexes between CN radicals and solvent molecules. 23,24 The current study extends these prior investigations to reactions of CN radicals in acetonitrile (CH3CN or CD3CN), which is chosen because it is a more strongly interacting solvent than chloroform and dichloromethane.…”
Section: Introductionmentioning
confidence: 99%